2012
DOI: 10.1111/j.1540-6520.2012.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Extending Women's Entrepreneurship Research in New Directions

Abstract: The dramatic expansion of scholarly interest and activity in the field of women's entrepreneurship within recent years has done much to correct the historical inattention paid to female entrepreneurs and their initiatives. Yet, as the field continues to develop and mature, there are increasingly strong calls for scholars to take their research in new directions. Within this introduction to the special issue, we expand upon the reasons for this call, describe who responded, and summarize the new frontiers explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
308
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 419 publications
(339 citation statements)
references
References 45 publications
5
308
0
7
Order By: Relevance
“…Historically, research into women's entrepreneurship has been fraught with methodological problems and limitations in theoretic development (De Bruin et al, 2007;Hughes et al, 2012;Jennings & Brush, 2013;Marlow & Patton, 2005). The present study's research approach enables us to extend theorizing and overcome methodological limitations.…”
Section: Research Approachmentioning
confidence: 97%
See 1 more Smart Citation
“…Historically, research into women's entrepreneurship has been fraught with methodological problems and limitations in theoretic development (De Bruin et al, 2007;Hughes et al, 2012;Jennings & Brush, 2013;Marlow & Patton, 2005). The present study's research approach enables us to extend theorizing and overcome methodological limitations.…”
Section: Research Approachmentioning
confidence: 97%
“…The consequence of such barriers to financing is that the business underperforms. The impact of hidden (unconscious) biases in finance distribution such as gender stereotypes has been researched, but empirically, prior studies have been limited to surveys and other methods, which restricts investigating how closed-room discussions are executed and the role and character of stereotyping in decision making (see Alsos & Ljunggren, 2016;De Bruin, Brush, & Welter, 2007;Hughes, Jennings, Brush, Carter, & Welter, 2012;Jennings & Brush, 2013). Other studies have reported on the propensity of individual decision makers or the general public to stereotype (Fay & Williams, 1993;Gupta, Goktan, & Gunay, 2014;Gupta, Turban, & Pareek, 2013), but no study has investigated stereotyping among a group of decision makers that jointly make funding decisions.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, we have witnessed an expansion of scholarly interest in the field of women's entrepreneurship (Ahl 2006;Calas, Smircich, and Bourne 2009;Hughes et al 2012;Chiang, Low, and Collins 2013;Gutiérrez, Fuentes, and Ariza 2014;Langevang et al 2015). As the topic matures, scholars have stressed the need for new research directions 'to capture more and richer aspects of women's entrepreneurship' (Ahl 2006, 610;Calas, Smircich, and Bourne 2009;Hughes et al 2012;Gutiérrez, Fuentes, and Ariza 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, authors have stressed the need for a collective focus on women entrepreneurs to enable an understanding of contextual and cultural variables rather than an individualist focus (Essers, Doorewaard, and Benschop 2013). Research further points to the need for explorative qualitative rather than analytic quantitative techniques for a more robust understanding of the phenomenon of women's entrepreneurship to 'shed light on the actions and efforts in entrepreneurship unique to women' (Ahl 2006;Brush and Cooper 2012, 5;Hughes et al 2012). In addition, the entrepreneurship literature has been criticized for neglecting the impact of family dynamics on entrepreneurial processes, despite family and business dynamics being highly interrelated (Aldrich and Cliff 2003;Jennings and McDougald 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation